The effect of cocoa powder on the development of oxidative rancidity in peanut products - Peterson, Hilary (Kansas State University, 2013)
The objective of this study was to observe the effect of natural cocoa powder versus 200 ppm of tocopherols on delaying the onset of oxidative rancidity in peanuts, peanut butter, and peanut oil. The samples were obtained from a single lot of blended Runner peanuts after roasting, grinding, and pressing. The samples were treated within a week of initial roasting with either 200 ppm of mixed tocopherols or 2.5% cocoa powder. The development of oxidation was monitored by peroxide value (PV) and gas chromatography monitoring of hexanal development. The peanut butter samples were assessed by a professional sensory panel using descriptive analysis for the development of rancidity. The data was analyzed using JMP SAS software. In peanuts, the cocoa powder sample developed significantly lower levels of oxidation identifiers than the tocopherol or control samples. In peanut oil, there was no significant difference in levels of oxidation identifiers between the treatments. In peanut butter, the PV was significantly higher in the tocopherol sample than the cocoa powder or control samples, but no significant difference was observed in hexanal. The results of the sensory analysis indicated that the cocoa powder depressed the perception of both positive and negative attributes compared to the tocopherol and control samples. This study showed that cocoa powder may be a more effective preservative than an untreated sample or a sample treated with 200 ppm of tocopherols in peanuts and peanut butter; however, cocoa powder at 2.5% w/w basis did not perform as a significant antioxidant in peanut oil.
Keywords: Cocoa powder; Antioxidant; Preservative; Peanuts; Food Science (0359)